ÃNDICES DE CONSUMO E UTILIZAÇÃO DE CULTIVARES DE AMOREIRA POR Bombyx mori L. - Bortoli, Sergio Antonio de; Montagna, Marco Aurélio; Miranda, José Ednilson; Murata, Afonso Takao; Takahashi, Roque (REVISTA DE AGRICULTURA, 2015)
ÃNDICES DE CONSUMO E UTILIZAÇÃO DE CULTIVARES DE AMOREIRA POR Bombyx mori L.